Study of changes in the mechanical and thermal conductive properties of AlN ceramics exposed to heavy ion irradiation - Kozlovskiy, A.L. (Recent Contributions to Physics, 2022)
The paper presents the results of study of the effect of irradiation with heavy Ar8+, Kr15+ and Xe22+ ions with energies of 70, 150 and 230 MeV, respectively, on the stability of mechanical properties, in particular, hardness and wear resistance, as well as thermal conductivity, depending on irradiation fluence. The interest in this research topic is due to the wide prospects for the use of nitride ceramics as the basis for structural materials for nuclear and thermonuclear energy, exposed to ionizing radiation, in particular, particles - fragments of fission of uranium nuclei. During the experiments, dose dependences of changes in strength, mechanical and heat-thermal conductive properties were obtained. It has been established that the decrease in thermal conductivity has a pronounced dependence on both the energy of incident ions and the radiation dose. The obtained dependencies can later be used in the forecasting and design of nuclear power plants, in which it is planned to replace traditional materials with new classes, including ceramics or composite structures.
Keywords: nitride ceramics; radiation defects; strength; thermal conductivity; degradation